2013
DOI: 10.1128/aac.00889-13
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Influence CDR1 Efflux Pump Activity, Hog1-Mediated Oxidative Stress Pathway, Iron Homeostasis, and Ergosterol Levels in Candida albicans

Abstract: dMitochondrial dysfunction in Candida albicans is known to be associated with drug susceptibility, cell wall integrity, phospholipid homeostasis, and virulence. In this study, we deleted CaFZO1, a key component required during biogenesis of functional mitochondria. Cells with FZO1 deleted displayed fragmented mitochondria, mitochondrial genome loss, and reduced mitochondrial membrane potential and were rendered sensitive to azoles and peroxide. In order to understand the cellular response to dysfunctional mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 92 publications
5
68
0
Order By: Relevance
“…7B). These results confirmed the existence of a close relationship between plant sterol metabolism and Fe homeostasis, a connection that is well established in other organisms such as fungi (Craven et al, 2007;Blatzer et al, 2011;Hosogaya et al, 2013;Thomas et al, 2013;Chung et al, 2014;Vasicek et al, 2014) but is much less known in plants (Urbany et al, 2013). In general, depletion of sterol biosynthesis has been correlated with both higher membrane permeability and increased uptake of metal ions in roots, although the underlying molecular mechanism remains unknown (Diener et al, 2000;Khan et al, 2009;Urbany et al, 2013;Wagatsuma et al, 2015).…”
Section: Reduced Levels Of Major Sterols Alter Fe Homeostasissupporting
confidence: 67%
“…7B). These results confirmed the existence of a close relationship between plant sterol metabolism and Fe homeostasis, a connection that is well established in other organisms such as fungi (Craven et al, 2007;Blatzer et al, 2011;Hosogaya et al, 2013;Thomas et al, 2013;Chung et al, 2014;Vasicek et al, 2014) but is much less known in plants (Urbany et al, 2013). In general, depletion of sterol biosynthesis has been correlated with both higher membrane permeability and increased uptake of metal ions in roots, although the underlying molecular mechanism remains unknown (Diener et al, 2000;Khan et al, 2009;Urbany et al, 2013;Wagatsuma et al, 2015).…”
Section: Reduced Levels Of Major Sterols Alter Fe Homeostasissupporting
confidence: 67%
“…In fact, Thomas et al found a connection between the upregulation of genes that are involved in iron assimilation such as SIT1 and RBT5 and the downregulation of ERG3 and ERG11 in a C. albicans mutant with an impaired mitochondrial function (57). Those investigators also reported that alteration of iron levels in the mitochondrial mutant led to increased susceptibility to H 2 O 2 via the activity of an impaired high-osmolarity glycerol (HOG) pathway and high cellular ROS (57). These findings suggest that the increased susceptibility to oxidative stress shown by AmB-R strains of C. albicans with ERG gene deletions (55) could be caused by a perturbation of the HOG1 MAP kinase pathway that controls respiratory metabolism and is essential in the oxidative stress response (58).…”
Section: The Development Of Amb Resistance In Eukaryotic Pathogensmentioning
confidence: 99%
“…Notably, in the AmB-R strains of C. albicans with deleted ERG3/ERG11 genes, a set of genes that are typically induced under iron starvation conditions are constitutively expressed, reflecting the fact that this stress is highly linked to ergosterol homeostasis (57). In fact, Thomas et al found a connection between the upregulation of genes that are involved in iron assimilation such as SIT1 and RBT5 and the downregulation of ERG3 and ERG11 in a C. albicans mutant with an impaired mitochondrial function (57). Those investigators also reported that alteration of iron levels in the mitochondrial mutant led to increased susceptibility to H 2 O 2 via the activity of an impaired high-osmolarity glycerol (HOG) pathway and high cellular ROS (57).…”
Section: The Development Of Amb Resistance In Eukaryotic Pathogensmentioning
confidence: 99%
“…As a second example, mitochondrial fusion/fission mutants of C. albicans display fragmented mitochondria and mitochondrial genome loss. 20 A consequence of ATP decline in these mutants was an increase in susceptibility to azoles probably due to a reduced activity of energy-requiring efflux pumps. Our published data also correlate a loss of CI with increased susceptibility to fluconazole.…”
Section: Complex I Subunit Proteins As Drug Targetsmentioning
confidence: 99%
“…18 Two examples are provided. 19,20 The RAS-Cyr-PKA pathway is a major regulator of filamentation, biofilm formation, and virulence in C. albicans. Functioning of the Ras1-Cyr-PKA pathway requires a high cell energy status.…”
Section: Complex I Subunit Proteins As Drug Targetsmentioning
confidence: 99%